Antihypertensive effect of sinapine extracted from rapeseed meal in 2K1C hypertensive rats - Gaoyuan Yang; Lin Zhu; Yu Wang; Yang Yu; Xiaoguang Liu; Jingbo Xia; Yunjie Yang; Huiguo Wang; Baomin Feng (Scientific Reports)
Abstract To extract sinapine from rapeseed meal and investigate its antihypertensive function and mechanism. Blood pressure was measured before and after sinapine administration to evaluate sinapine’s immediate antihypertensive function. Twokidney, oneclip (2K1C) hypertensive rats were given sinapine for four weeks, with weekly blood pressure monitoring. The renin angiotensin aldosterone system (RAAS), including the levels of renin, angiotensin I (Ang I), angiotensin II (Ang II), aldosterone (ALD), angiotensin-converting enzyme (ACE) and other molecules related to blood pressure, such as NO, prostacyclin (PGI2), endothelin-1 (ET1), and thromboxane A2 (TXA2), were measured in rat blood. The impact of sinapine on vascular endothelial cell (A10) calcium and potassium channels was assessed using the patch-clamp technique. One-time or long-term administration of sinapine significantly reduced the rats’ systolic blood pressure (SBP), diastolic pressure (DBP), and mean blood pressure (MBP). Sinapine also decreased the levels of Ang II and ALD. Furthermore, sinapine effectively inhibited ACE activation, increased NO levels, and blocked L-type calcium channels. Sinapine has an antihypertensive function and achieves this process through multiple targets.